PERAN STRATEGIS SCRUM MASTER PADA PENGEMBANGAN PERANGKAT LUNAK DI SEBUAH INDUSTRI - R Wisnu Prio Pamungkas; Beatric Stevany Zebua; Aulia Nada Azizah (P3M Politeknik Negeri Indramayu, 2023)
At present, in latest industrial era, to realize the success of Integrated Product Development, many industries are competing to find innovative project design methodologies that are able to adapt to developments and consumer behavior that often changes from time to time amid the development of science and technology in dealing with competition in the 4.0 revolution era. When the industry is required to periodically produce its products and services quickly by adjusting to market movements, product development can be inspired through the Agile Project Management framework approach with the Scrum method. Not a few of the information technology (IT) industry has begun to transform to adapt the Scrum Method because of its adaptive nature for the purpose of team-based iterative software development. However, the limitations and the lack of studies in exploring the nature and characteristics of Scrum currently make many people still not too familiar with the existence and essence of a Scrum Master, especially the nature and characteristics known as a servant leader (Servant-Leader). The aim of this research is to understand the true role of a Scrum Master who is at the heart of the application of the Scrum method in software development in an industry, so that it is expected to help realize the fulfillment of excellent and optimal services that are faster and more agile.